Starting and running a restaurant - Pennette, Jody; Keyser, Elizabeth (New York, NY : Alpha Science International Ltd, 2015)
Around 90% of all new restaurants fail in the first year of operation. Many owners think they have the perfect idea, but they have terrible business plans, location, or other issues. Idiot's Guides: Starting and Running a Restaurant shows budding restauranteurs the basics of honing in on a concept to gathering start-up capital to building a solid business plan. You will also learn how to choose a great restaurant location, select an appealing design, compose a fantastic menu, and hire reliable managers and staff. In this book, you get: introduction to basic requirements of starting a restaurant such as time management, recognizing your competition, choosing your restaurant concept, and making it legal, information on building a solid business foundation such as a solid business plan, a perfect location, where to find investors, and securing loans, suggestions on how to compose the perfect menu, laying out the front and back of house and bar, and choosing the must-have necessities such as security alarms and fire prevention, techniques on how to hire and train your staff, purchasing or renting supplies, understanding costs and setting up your financial office, and using social media as a marketing tool, secrets for keeping your customers returning, running a safe restaurant, managing employees, and building your PR sales plan and pre-opening checklists to ensure everything is ready by opening day.
Part 1: An introduction to the restaurant business -- 1.Why open a restaurant? -- 2.Defining your market relevancy -- 3.Distilling your concept -- 4.4.Licenses and legalities -- Part 2: Building your restaurant's foundation -- 5.Creating a solid business plan -- 6.Choosing a location -- 7.Negotiating your lease -- 8.Finding your cash -- Part 3: Setting up your restaurant -- 9.Composing your menu -- 10.Designing the front of the house -- 11.Setting up your bar and beverage systems -- 12.Laying out the back of the house -- 13.Restaurant maintenance -- Part 4: An owner's role in management -- 14.Hiring your staff -- 15.Purchasing supplies -- 16.Running your office -- 17.Understanding costs -- 18.Beginning your marketing blitz -- Part 5: Running your restaurant -- 19.Fostering a culture of hospitality -- 20.Running a safe restaurant -- 21.Managing and training your employees -- 22.Growing your business.
Includes index.
Keywords: RESTAURANT MANAGEMENT